2019
DOI: 10.1248/bpb.b19-00537
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Light Shielding on Photo-Degradation of Dacarbazine during the Preparation Process

Abstract: Dacarbazine (DTIC) is converted to the photo-degradation product 4-diazoimidazole-5-carboxamide (Diazo-IC) by light. Diazo-IC production is often responsible for the pain reactions observed during peripheral intravenous infusion of DTIC in clinical settings. Although light shielding during infusion decreases the photo-degradation of DTIC, its usefulness for the preparation of DTIC has not yet been fully clarified. The aim of this study was to investigate the light conditions during the preparation of DTIC solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…These results have demonstrated that environmental matrices can produce different transformation products and that the experimental conditions in photodegradation studies are critical and should, therefore, be as similar as possible to those of environmental systems [ 81 ]. Dacarbazine, an alkylating agent commonly used in combination with other chemotherapeutic agents for the treatment of metastatic malignant melanomas, Hodgkin’s lymphoma and pheochromocytomas, is converted by light into 4-diazoimidazole-5-carboxamide [ 103 ]. This photo-transformation product is often responsible for the pain reactions observed during peripheral intravenous infusion during clinical application.…”
Section: Stability Of Anticancer Prodrugsmentioning
confidence: 99%
“…These results have demonstrated that environmental matrices can produce different transformation products and that the experimental conditions in photodegradation studies are critical and should, therefore, be as similar as possible to those of environmental systems [ 81 ]. Dacarbazine, an alkylating agent commonly used in combination with other chemotherapeutic agents for the treatment of metastatic malignant melanomas, Hodgkin’s lymphoma and pheochromocytomas, is converted by light into 4-diazoimidazole-5-carboxamide [ 103 ]. This photo-transformation product is often responsible for the pain reactions observed during peripheral intravenous infusion during clinical application.…”
Section: Stability Of Anticancer Prodrugsmentioning
confidence: 99%
“…Nevertheless, the most promising method for engineering programmable nanoscale drug delivery vehicles is to encode stimuli responsiveness and if the stimulus is external light stimuli, then photomanipulation will allow for spatial and temporal precision in drug delivery . Therefore, this class of drug delivery systems (DDSs) has recently acquired prominence in providing spatiotemporal control over the release of anticancer drugs at the tumor site upon light exposure . However, the inherent limitations of ultraviolet (UV) and visible light include low penetration depth, phototoxicity, insufficient photostability of the chromophore/fluorophore, and nonspecific background fluorescence, which limit its use in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…DTIC is an anticancer drug indicated for the treatment of metastatic malignant melanoma and soft tissue sarcoma, being also used in the treatment of early Hodgkin lymphoma. , Although it may be ionized, this API is commercialized in a neutral form as an intravenous formulation, exhibiting pH-dependent aqueous solubility and a pronounced photodegradation when exposed to light. , The main photodegradation product, 2-azahypoxanthine (2-AZA), is pharmacologically inactive and further responsible for some adverse reactions. , To reduce photodegradation, freshly prepared DTIC solutions protected from light must be intravenously administered as quickly as possible. , Recently, Uchida et al developed a photochemically stabilized formulation of DTIC using reactive oxygen species. The lack of scientific reports on this line reinforces the idea that the emergence of alternative and safe technologies to overcome DTIC issues remains highly demanded.…”
Section: Introductionmentioning
confidence: 99%
“… 20 , 21 To reduce photodegradation, freshly prepared DTIC solutions protected from light must be intravenously administered as quickly as possible. 22 , 23 Recently, Uchida et al 24 developed a photochemically stabilized formulation of DTIC using reactive oxygen species. The lack of scientific reports on this line reinforces the idea that the emergence of alternative and safe technologies to overcome DTIC issues remains highly demanded.…”
Section: Introductionmentioning
confidence: 99%